Nouvelles perspectives sur l’accentuation des emprunts en anglais contemporain - Pierre Fournier (Itinéraires)
This article investigates the stress patterns of loanwords in contemporary English, and in particular the primary stress location (/1/). Using three source languages (Italian, Japanese and French), it turns out that three distinct aspects of phonological transfers are highlighted and that the creation of a typology of loanwords in English, which would be based on the connection between the source language and the target language is made possible with the parameters of faithfulness/replication and assimilation/adaptation.